2022
DOI: 10.1186/s41039-022-00198-8
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology supporting English learning among Indonesian university students

Abstract: Worldwide, information technology now plays a substantial role in the daily life of most people, whether in the developed world or in developing countries, such as Indonesia. In this fourth most populated country in the world, information technology is widely used for everyday communications and entertainment purposes, as well as for supporting education. Using a survey of 496 students enrolled in a university in Jakarta, this paper reports on a study aimed at assessing the experiences of young Indonesian stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
2
18
0
3
Order By: Relevance
“…However, by utilizing educational applications, teachers could save more time funded with valid and trustable student reading skills assessments. Meanwhile, it is also necessary to equip English teachers with skills in utilizing technology in their teaching (Hidayat et al, 2022). In the current study, Google Form dominates the use of media to assess students' reading skills.…”
Section: Discussionmentioning
confidence: 97%
“…However, by utilizing educational applications, teachers could save more time funded with valid and trustable student reading skills assessments. Meanwhile, it is also necessary to equip English teachers with skills in utilizing technology in their teaching (Hidayat et al, 2022). In the current study, Google Form dominates the use of media to assess students' reading skills.…”
Section: Discussionmentioning
confidence: 97%
“…Deep learning is a special field of study that aims to promote effective learning and to insist on the "unity of knowledge and action" through the interaction and interaction of learners, environment, artifacts, and active learning guided by strong intrinsic motivation [11][12][13]. It is "meaning-making" learning characterized by conceptual transformation, integrated understanding, and creative cognitive restructuring.…”
Section: P(v)and9; � 􏽘mentioning
confidence: 99%
“…Regarding previous research on online learning platforms, it has been found that: (a) virtual platforms can be used in favor of deep learning [6], (b) online learning can generate significant learning in times of pandemic [7], (c) there is a positive psychological response in favor of the use of the online learning platform [8], (d) virtual platforms are effective for learning a second language such as English [9], ( e) they are successful in the educational process of classical sciences, such as medicine [10,11], (f) virtual platforms increase educational performance, student engagement, evaluation methods, and collaborative learning [12,13]; and (g) the contribution of the metaverse and augmented reality in student satisfaction and interaction in favor of the learning process [14].…”
Section: -Introductionmentioning
confidence: 99%